THE STUDY OF NUTRITIONAL REQUIREMENTS IN SECOND TRIMESTER W.S.R. GARBHINI PARICHARYA ACCORDING TO SUSHRUTACHARYA - Balpande, *Kanchan; Nikumbh, Milind B.; Rathod, Sanjay T.; Dawre, Manisha (International Journal of Ayurveda and Pharma Research, 2017)
It is the need of an hour to have healthy pregnancies in Indian population as the normal nutritional requirements in maternal periods of women in India are not getting fulfilled, so as the malnourished and birth defective children are born. Out of three trimesters of pregnancy in second trimester nutrition need are higher than estimated nutrition requirement for non pregnant women which is less in first trimester. As per the modern science there are lot many nutritional deficiencies occurring in second trimester which causes serious health hazards in mother as well in fetus. The main deficiencies in second trimester of pregnancy are protein, folic acid, calcium, iron, vitamin D, thiamine, vitamin A. Ancient Ayurveda prescribes some set of guidelines which can help make this time more easy for the women. Ayurveda has given proper regimens of diet and life style in during different stages of pregnancy. This paper talks about second trimester of pregnancy because in this all organ starts to appear according to Ayurvedic Samhitas and modern aspects also. It is given in Mansanumasik Garbhini Paricharya which is mentioned in Ayurvedic Samhita, the regime for the pregnant women. It is similar to the modern science diet to the pregnant women. Therefore this is a small effort to find out the exact concept of Garbhini Paricharya given by Aacharya sushruta is nutritionally a complete supplement for Garbhini.